Single pivotal trials with few corroborating characteristics were used for FDA approval of cancer therapies - Aviv, L; Speich, B; Matthias, B; Francesco, S; Heiner C, B; Arnav, A; John P.A., I; Tiago V., P; Benjamin, K; Lars G, H (Elsevier, 2019)
Background and objective Novel cancer therapies are often approved with evidence from a single pivotal trial alone. There are concerns about the credibility of this evidence. Higher validity may be indicated by five methodological and statistical characteristics of pivotal trial evidence that were described by the U.S. Food and Drug Administration (FDA), which may corroborate the reliance on a single trial alone for approval decisions. Study design We did a metaepidemiologic evaluation of all single pivotal trials supporting FDA approval of novel drugs and therapeutic biologicals for cancers between 2000 and 2016. For each trial, we determined the presence of these five characteristics, which we operationalized as (1) large and multicenter trial (≥200 patients; more than one center); consistent treatment benefits across (2) multiple patient subgroups (in view of FDA reviewers), (3) multiple endpoints (including overall survival, progression-free survival, response rate, health related quality of life), and (4) multiple treatment comparisons (e.g., multi-arm studies); and (5) “statistically very persuasive” results (P-values <0.00125). Results Thirty-five of 100 approvals were based on evidence from a single pivotal trial without any further supporting evidence on beneficial effects (20 randomized controlled trials and 15 single-arm trials). The number increased substantially from one approval before 2006 to 23 after 2011. Sixty-six percent (23/35) of the trials were large multicenter trials (median 301 patients and 63 centers). Consistent effects were demonstrated across subgroups in 66% (23/35), across endpoints in 43% (15/35), and across multiple comparisons in 3% (1/35). Very low P-values for the primary endpoint were seen in 34% (12/35). At least one of the corroborating characteristics was present in 94% (33/35) of all approvals, two or more were present in 54% (19/35), and none had all characteristics. Conclusions Single pivotal trials typically have some of the corroborating characteristics, but often only one or two. These characteristics need to be better operationalized, defined, and reported and whether single trials with such characteristics provide similar evidence about benefits and harms of novel treatments as multiple trials would do needs to be shown.